Optimalisasi Pemanfaatan Limbah Organik Menjadi Produk Multipurpose Cleaner Dalam Upaya Pemberdayaan Perempuan di Kel. Mojotengah, Kec.Menganti , Kota Gresik - Shinta Wurdiana Rhomadona; Meika Ayu Cahya Ningrum (Universitas Merdeka Surabaya, 2022)
The waste generated by people's daily activities consists of organic and non-organic waste. Nearly 70% of the waste that is disposed of in landfills is organic waste, which causes an unpleasant odor and the decomposition of this organic waste can produce methane gas which is the cause of global warming. Mojotengah Village, Menganti District has potential in environmental cleanliness with the existence of a waste bank institution with the name